Levantamento da herpetofauna do Parque SESC Serra Azul, Mato Grosso, Brasil - Gonçalves, José Nilton de Araújo (2023)
Despite the high diversity and ecological relevance of amphibians and reptiles, there are significant gaps in our knowledge regarding the occurrence, biology, and distribution of species from these groups in different parts of Brazil, particularly in Mato Grosso. In order to increase our understanding of the Cerrado's herpetofauna, we present a species list of amphibians and reptiles from the Parque SESC Serra Azul in the western portion of the Cerrado. We also provide data on seasonal variation and the influence of forest phytophysiognomy (Riparian Forest and Semideciduous Dry Forest) on the communities. Fieldwork was conducted from February 2022 to January 2023, and sampling methods included pitfall traps, funnel traps, active search, chance encounters, and third-party records. In total, 2,432 individuals from 99 species were recorded, with 36 amphibian species and 63 reptile species. The observed and estimated species accumulation curves for amphibians indicated a stabilization trend, with 84% of the expected richness being recorded. However, the curves for reptiles did not show this stabilization. Active search was the most effective method for finding amphibians, accounting for 97% of the records, while third-party collection was the most utilized method for reptiles, representing 62% of the records. Analyses comparing the forest formations revealed no significant differences in richness, abundance, and composition among the amphibian communities. On the other hand, reptile abundance was higher in the Semideciduous Dry Forest compared to the Riparian Forest. Seasonal analyses suggested that amphibians and reptiles respond differently to seasonal variations. Overall, the results indicate that the Parque SESC Serra Azul harbors a representative diversity of amphibians and reptiles from the Cerrado, despite the heterogeneity of the study area, which includes pastures and more open formations. Therefore, this study contributes to the knowledge of the region's amphibian and reptile fauna, providing information on their occurrence, biology, and distribution in the Parque SESC Serra Azul.